Dynamic Capability Theory: Digital Transformation as a Sustainable Competitive Performance Strategy for MSMEs - Eskasari Putri; Ashar Mukhammad Akbar; Tariq Tawfeeq Yousif Alabdullah; Kholid Jundi Ar-Ridho; Arief Surya Adhi; Windi Amelia Adindaningtyas Putri (Riset Akuntansi dan Keuangan Indonesia, 2025)
This study examines the influence of information technology (IT) infrastructure capabilities, business and IT planning capabilities, proactive attitudes toward IT on digital transformation, and their impact on the sustainable competitive performance of MSMEs in Indonesia. This study uses a quantitative approach with data collection through a questionnaire with 783 MSME respondents. Data analysis uses the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results show that IT infrastructure capabilities, business and IT planning capabilities, and proactive attitudes toward IT have a positive and significant influence on digital transformation. Furthermore, digital transformation has also been shown to have a significant influence in improving sustainable competitive performance, such as productivity, operational efficiency, and customer relationships. These findings emphasize the importance of synergy between strategic planning and technological readiness, as well as a proactive digital culture in the MSME environment. This study provides empirical contributions from the context of developing countries and offers practical recommendations for stakeholders in promoting MSME digital readiness.